2017
DOI: 10.1001/jamainternmed.2017.3631
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Characteristics of US Medicare Spending on Repository Corticotropin

Abstract: Ms Cole had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…From 2011 to 2015, spending on corticotropin in the US Medicare program increased 10-fold, totaling more than $1 billion during this period. 27 In 2015 alone, Medicare spent more than $500 million on corticotropin, making it one of the most expensive drugs paid for by the program. 28 The continued growth in corticotropin use is peculiar given its very high cost, widespread negative media coverage, and notable lack of evidence supporting its use over lowercost synthetic corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…From 2011 to 2015, spending on corticotropin in the US Medicare program increased 10-fold, totaling more than $1 billion during this period. 27 In 2015 alone, Medicare spent more than $500 million on corticotropin, making it one of the most expensive drugs paid for by the program. 28 The continued growth in corticotropin use is peculiar given its very high cost, widespread negative media coverage, and notable lack of evidence supporting its use over lowercost synthetic corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to SRNS, one study with 24 FSGS patients reported complete or partial remission in 29% (7/24) after initiation of ACTH gel treatment, suggesting its possibility as a treatment option [ 77 ]. However, the high expense of ACTH, the relative lack of evidence [ 133 ] and recent reports on its prescription having been influenced by financial conflict of interest [ 134 , 135 ] should prevent hasty recommendations on this drug being made.…”
Section: Non-immunologic Therapiesmentioning
confidence: 99%
“…28 For example, total Medicare spending on repository corticotropin, a pediatric antiseizure medication with limited effectiveness over less costly alternative medications in adults, increased nearly 13-fold, from $49.5 million in 2011 to $636 million in 2016, with the cost per claim increasing from $33,621 to $49,442 during that period. [32][33][34][35][36] In contrast to these U.S. circumstances, most other countries use price regulations (e.g., reference pricing, health technology assessment) to control drug costs. 37 Additional manufacturer practices increase U.S. payer outlays.…”
Section: ■■ Foundation Of Drug Benefit Management In Early Pbm Business Modelsmentioning
confidence: 99%